Daydream eaudiobook - Grace, Hannah (Maple Hills, 2024)
#1 New York Times bestseller! The third in the New York Times bestselling Maple Hills series follows fan-favorite Henry and a bookish fellow student who come up with a plan to help them both overcome their respective challenges in a difficult year. When his procrastination lands him in a difficult class with his least favorite professor, Henry Turner knows he's going to have to work extra hard to survive his junior year of college. And now with his new title of captain for the hockey team—which he didn't even want—Henry absolutely cannot fail. Enter Halle Jacobs, a fellow junior who finds herself befriended by Henry when he accidentally crashes her book club. Halle may not have the romantic pursuits of her favorite fictional leads, but she's an academic superstar, and as soon as she hears about Henry's problems with his class reading material, she offers to help. Too bad being a private tutor isn't exactly ideal given her own studies, job, book club, and the novel she's trying to write. But new experiences are the key to beating her writer's block, and Henry's promising to be the one to give them to her. They just need to stick to their rule book. Oh, and not fall in love.